Understanding the effects of ball orientation in Rugby Union place kicking: the preferences of international kickers and the kinematics of the foot-ball impact - Sam Jones (Sports Biomechanics, 2022)
Rugby Union place kicking is influential to match outcome. Previous research has analysed kicker motion prior to ball contact in detail, but ball orientation and the impact phase are typically ignored. This study aimed to firstly identify the ball orientations used by international place kickers, and secondly to experimentally analyse the foot–ball interaction in trained kickers using different ball orientations. 25.5% of international kickers used an upright ball orientation, 27.5% used a diagonal orientation, and 47.1% used a horizontal orientation. However, ball orientation preference was not significant in predicting kick outcome in a binomial logistic regression model. To address the second aim, ball orientation was experimentally manipulated and lower limb and ball kinematics were captured using high-speed (4000 Hz) video. Whilst impact location on the ball differed significantly between most ball orientation conditions, the impact location relative to the global vertical was largely consistent across all conditions. This was likely due to kickers adopting very consistent lower limb kinematics, although the shank and ankle angles at impact were affected by ball orientation condition for some kickers. Impact durations also differed between some conditions although this did not appear to affect the impact efficiency.